Cilia and flagella - Dentler, William; Witman, George (Methods in cell biology, 1995)
Cilia and Flagella presents protocols accessible to all individuals working with eukaryotic cilia and flagella. These recipes delineate laboratory methods and reagents, as well as critical steps and pitfalls of the procedures. The volume covers the roles of cilia and flagella in cell assembly and motility, the cell cycle, cell-cell recognition and other sensory functions, as well as human diseases and disorders. Students, researchers, professors, and clinicians should find the book's combination of "classic" and innovative techniques essential to the study of cilia and flagella.